Exploring the current state of technology transfer in the United States: perspectives and improvement strategies from the experts - Eidlisz, Jordan; von Simson, Isabelle; Gold-von Simson, Gabrielle (Frontiers in Research Metrics and Analytics, 2024)
Technology transfer (TT) is a necessary, yet complex process to convey and disseminate scientific knowledge to the commercial sector. However, multiple barriers in TT can impede commercialization and innovative progress. To cultivate a deeper understanding, we conducted 5 interviews with strategic, elite leaders in different areas of TT in the United States. Experts shared their perspectives on the current state of TT, what needs improvement, and potential solutions to enhance the TT landscape, with a focus on biotechnology and medical devices. The formation of strong management teams, a comprehension of the regulatory, reimbursement, and funding pathways and policies, and thorough market assessments were noted as key aspects for venture success. Collaboration with Technology Transfer Offices (TTOs), industry experts, and strategic partners are also essential to support academic innovators and guide them throughout the complex commercialization process. There is agreement that a venture should have a defined vision and clear goals with a robust business case for the innovation; early involvement of TTOs is essential. Comprehension of the complexities and key facets of TT, while also streamlining the process, will better position biomedical innovators for success.